TEL/AML1-positive patients lacking TEL exon 5 resemble canonical TEL/AML1 cases - Zaliova, Marketa; Meyer, Claus; Cario, Gunnar; Vaskova, Martina; Marschalek, Rolf; Stary, Jan; Zuna, Jan; Trka, Jan (Pediatric blood & cancer, 2011)
BACKGROUND: The TEL/AML1 fusion gene which represents the most frequent genetic abnormality in childhood ALL, usually results from genomic breakpoints in TEL intron 5 and AML1 intron 1 or 2. At the protein level, the helix-loop-helix domain and exon 5-coded central region of TEL are typically fused to almost entire AML1 including DNA-binding domain. PROCEDURE: We identified two ALL patients with genomic breakpoints within TEL intron 4 resulting in variant TEL/AML1 fusion lacking the TEL exon 5-coded central region. This region was supposed to play an important role in TEL/AML1 function, particularly in TEL/AML1-mediated transcriptional repression of AML1 targets. We aimed at investigating the impact of the loss of this region on disease behavior and TEL/AML1 function. We compared clinical and biological characteristics, treatment response, and outcome of the variant versus classical TEL/AML1 cases, analyzed genome wide gene expression profiles and performed reporter gene assay. RESULTS: No distinct differences between variant and classical TEL/AML1 cases were observed including gene expression profiling and detailed immunophenotyping. By using reporter gene assay, we showed that the loss of the central region does not influence the TEL/AML1-mediated transcriptional repression. CONCLUSIONS: The deletion of the central region did not affect the TEL/AML1-specific phenotype; we did not find any relevant differences in clinical and biological features when variant versus classical TEL/AML1-positive cases were compared. Thus, our data does not support hypothesis that the central region of TEL is indispensable for TEL/AML1 driven leukemogenesis.
Keywords: exony; exprese genu; Humans; sekvence nukleotidů; Gene Expression; dítě; In Situ Hybridization, Fluorescence; Molecular Sequence Data; Child; molekulární sekvence - údaje; fúzní onkogenní proteiny; polymerázová řetězová reakce s reverzní transkripcí; Blotting, Western; Exons; protein ETS, translokační varianta 6; lidé; Reverse Transcriptase Polymerase Chain Reaction; represorové proteiny; Oncogene Proteins, Fusion; předškolní dítě; Core Binding Factor Alpha 2 Subunit; Repressor Proteins; Base Sequence; hybridizace in situ fluorescenční; Adolescent; protoonkogenní proteiny c-ets; stanovení celkové genové exprese; Proto-Oncogene Proteins c-ets; akutní lymfatická leukemie; Gene Expression Profiling; protein PEBP2A2; western blotting; Child, Preschool; Precursor Cell Lymphoblastic Leukemia-Lymphoma; ETS Translocation Variant 6 Protein; mladiství